(3GNJUGQ GdSjQI GdfHhjIs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3CeG HO aEfi ENJUQJ aj gPG GdLRA eG jSgd Ydi GdeQjO MaXg ef PcQ fSH QShd Gddg Ud Gddg Ydjg hSde hUaJg ai Ndbg hNdbg hSjQJg , eMPha GdCSGfjO s
(3BNQgG (B:s
(3hBjGJ CcKQ ef Gf JMUi QhjfGgG hQCjfGgG ai fahSfG s
(3GfXQ GdbSe GdKGdK HQbe (B878s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281s
Keywords: (3GdJGQjNs